The Role of Melatonin and Leptin with gene expiration of ADCY3 in Obese people - Alsaady, Marwa M.; Maleek, Muthana I. (Journal of Neonatal Surgery, 2025)
Background: obesity is linked to early death and poses a severe danger to public health. Non-communicable diseases, including type 2 diabetes, cardiovascular conditions, high blood pressure, and various cancers, significantly contribute to the global health burden. Studying the genes, hormones, and proteins that has correlation with obesity will help explain why some people, even in identical situations, are more likely to become obese than others. Aim: Identify relationships between Melatonin and Leptin with gene expiration of ADCY3 gene and differences between obese and healthy individuals in obesity people. Method: This study was carried out in laboratories of College of Science, Wasit University in Iraq form November 2023 to July 2024.This study were include 80 peoples the ages (18-50) they were measuring the BMI of them . Fifty obese people (25 male and 25 female) they are diagnosed clinically. The control group consists of 30 apparently healthy individuals (15 male and 15 female). The current study was in agreement with hospital ethics and approvals from all participants. Measuring melatonin, leptin and Gene (ADCY3) expiration in obese and control groups by EIESA assay. Results: The Results was evaluated at (P ≤ 0.05) value, significantly higher (P= 0.034) mean levels of melatonin hormone in obese person (167.12±12.11) but in healthy control group (124.76±5.84).also, Significantly higher (P= 0.002) mean levels of leptin hormone in obese person (1.47± 0.061) but in healthy control group (2.35 ± 0.411).Mean level of ADCY3 were (1.29 ± 0.19) in obesity people and (2.01 ± 0.29) in healthy control group, data showed highly significantly (P= 0.001) decreasing of mean level of ADCY3 in obesity people when compared with healthy control group. Moreover results showed highly significant(r=0.360, p= 0.025) Positive correlation Leptin and Melatonin .Furthermore, highly negative correlation between ADCY3 and Melatonin (r=-0.503, p= 0.001), and ADCY3 and Leptin (r=-0.391, p= 0.004). Conclusions: It is concluded from the present study that the gene expression of ADCY3 and Leptin hormone, Melatonin hormone important roles in the development and severity of obesity.